Word Play: A History of Voice Interaction in Digital Games. Issue 2 (March 2020) - Allison, Fraser; Carter, Marcus; Gibbs, Martin
The use of voice interaction in digital games has a long and varied history of experimentation but has never achieved sustained, widespread success. In this article, we review the history of voice interaction in digital games from a media archaeology perspective. Through detailed examination of publicly available information, we have identified and classified all games that feature some form of voice interaction and have received a public release. Our analysis shows that the use of voice interaction in digital games has followed a tidal pattern: rising and falling in seven distinct phases in response to new platforms and enabling technologies. We note characteristic differences in the way Japanese and Western game developers have used voice interaction to create different types of relationships between players and in-game characters. Finally, we discuss the implications for game design and scholarship in light of the increasing ubiquity of voice interaction systems.